An analysis of client complaints and their effects on veterinary support staff. Issue 2 (19th January 2022) - Rogers, Charles W.; Murphy, Lisa A.; Murphy, Ruth A.; Malouf, Kylee A.; Natsume, Rachel E.; Ward, Briana D.; Tansey, Colleen; Nakamura, Reid K.
Abstract: Background: Veterinarians and support staff have been reporting the negative mental health effects from client complaints (CC). A previous study was performed evaluating these effects in veterinarians however no such study has been performed on veterinary support staff (VSS). Objectiv: The purpose of this study was to investigate the frequency and effects of CCs on VSS. Methods: A cross sectional anonymous survey using a web‐based questionnaire was created evaluating the frequency, type, and effects from CC. The survey was distributed to five different VSS Facebook groups and respondents provided demographic information and reported the frequency and effects of such complaints. Results: A total of 681 questionnaires were collected during the study period but 130 were incomplete and were excluded from analysis. This resulted in 551 completed questionnaires available for review. One hundred and ninety (34.4%) VSS reported being subject to a CC in the previous 6 months with cost of care the most common reason (78.6%). Two hundred and sixty VSS (47.2%) reported feeling depressed because of CCs made against them, 295 VSS (53.5%) stated CCs negatively affected their enjoyment of their job, and 146 (26.5%) have considered changing their career because of CCs. Conclusions: CC have detrimental effects on VSS career satisfaction, mental health and hospital practices. Further studies are warranted to mitigate the detrimental effects of CCs. Abstract : Table 2: Frequency and Type of Client Complaints.